ANALISIS SISTEM INFORMASI AKUNTANSI PENGGAJIAN KARYAWAN DALAM UPAYA MENDUKUNG EFEKTIFITAS PENGENDALIAN INTERNAL PERUSAHAAN (Studi Kasus PT Fajar Agung Desa Bengabing) - friska, Friska Nanda Pratiwi; kamilah, Kamilah k (Pusat Riset dan Inovasi Nasional, 2023)
An abstranct is a brief summary of a resea The payroll and wage accounting system is an important part because it can help companies in processing salary/wages payments, thereby preventing fraudulent actions. A good accounting system will affect the company's internal control. This study aims to analyze how the payroll accounting information system has been implemented by PT. Fajar Agung and how the payroll accounting information system supports internal control at PT. Fajar Agung. This study uses a qualitative approach with a descriptive method, which focuses on the payroll accounting information system at PT. Fajar Agung and the internal control system at PT.Fajar Agung. Data collection techniques in this study are using the observation method, documentation method and interview method.